Manajemen Pimpinan Wilayah Muhammadiyah Dalam Melaksanakan ‎Dakwah Multikultural di Sumatera Utara - Pangestu, Den Bagus; Soiman, Soiman; Indonesia, Soiman (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2024)
Muhammadiyah Regional Leadership Management involves planning and implementing activities to achieve objectives. Islam, which is ‎rahmatan li ‎al-'alamin (grace to all mankind), uses various approaches to Dawah, including multicultural Dawah. Muhammadiyah's multicultural Dawah aims to promote harmony in a diverse society while remaining tolerant of inevitable differences. The research method employed is qualitative. It aims to examine how the regional leadership of Muhammadiyah conducts multicultural Dawah. This research highlights four principles for implementing multicultural Dawah: planning, organizing, actuating, and monitoring. The dawah activities include Tabligh akbar, recitation, and seminars. Muhammadiyah regional leaders faced challenges in carrying out multicultural Dawah due to its movement being perceived as eccentric. The Muhammadiyah regional leadership faces conflicts while carrying out their activities.‎